Pengaruh Dukungan Emosional Keluarga terhadap Kejadian Depresi Pada Remaja: Keperawatan Keluarga, Depresi, Remaja - Karokaro, Tati Murni; Aprizal, Aprizal; Yanis, Amel; Hardisman, Hardisman (Jurnal Kesehatan Komunitas, 2025)
Depression in adolescents is a significant mental health problem. One factor that can influence the incidence of depression in adolescents is family emotional support. This study aims to examine the effect of family emotional support on depression in adolescents. The purpose of this study was to analyze the effect of family emotional support on the incidence of depression in adolescents and to evaluate the level of emotional support provided by families to adolescents. This study used a cross-sectional design with questionnaires distributed to 202 adolescents aged 15-21 years. Data were analyzed descriptively and with statistical regression tests to assess the relationship between family emotional support and the incidence of depression. As many as 78.7% of adolescents felt comfortable with family emotional support, but 32.18% reported that their families often did not ask about their condition. Overall emotional support reached 67.3%. The study also found that female adolescents were more susceptible to depression although age, gender, and education factors did not show a significant relationship. Family emotional support plays an important role in reducing the impact of depression in adolescents. Although overall emotional support is good, many adolescents feel they are not getting enough attention from their families. Family emotional support has an effect on preventing depression in adolescents. Families need to pay more attention to the emotional needs of adolescents and improve counseling services to help parents understand their children's emotional conditions.